Entrepreneurship in Africa (Volume 15) - Akinyoade, Akinyinka; Dietz, Ton; Uche, Chibuike (Brill, 2017)
Historically, entrepreneurs have always played a central role in the development of nation states. Aside from rentier states, which depend extensively on the availability of mineral resource rents, most economically prosperous nations in the world have strong, innovative and competitive business enterprises and entrepreneurs as the bedrock of their economic development and prosperity. It was arguably because of the above historical fact that the World Bank in 1989 declared that entrepreneurs will play a central role in transforming African economies. Chapters in this book contribute to our understanding of the theory, structure and practice of entrepreneurship in diverse African countries. Case studies examined include: African multinational banks and businesses, female entrepreneurs, culture and entrepreneurship, finance and entrepreneurship and SMEs. Contributors include: Akinyinka Akinyoade, Kenneth Amaeshi, Crescence Marie France Okah Atenga, Ton Dietz, Françoise Okah Efogo, Emiel L. Eijdenberg, Abel Ezeoha, Yagoub Ali Gangi, Miguel Heilbron, Uwafiokun Idemudia, Nsubili Isaga, Afam Ituma, Jane N. O. Khayesi, Rebecca I. Kiconco, Jerry Kolo, Peter Knorringa, Addisu Lashitew, André Leliveld, Marta Lindvert, Nnamdi Madichie, Hesham E. Mohamed, Knowledge C. Mpofu, Albogast Kilangi Musabila, Ayodeji Olukoju, Eunice Abam Quaye, Miriam Siun, Arthur Sserwanga, Rob van Tulder, Chibuike Uche and Jaap Voeten.